CONTENIDOS PROGRAMÁTICOS, LOGROS Y EVALUACIÓN EN UN SEMINARIO PARTICIPATIVO - Chavarría, Ana Lorena (2012)
This article considers the results from the evaluation NO SE SABE EL TIPO DE EVALUACIÓN POR TANTO QUEDA EN EL AIRE of a participatory seminar NAMED "Latin America at the Dawn of the New Millennium 2010". It mentions the application of a scientific instrument and accurate data, provided by the instrument developed for the quantification, interpretation and qualification DE QUÉ ASPECTOS of the course students  in relation to the objectives set for this model of humanistic studies, and program activities that impact primarily on the national and global environmental problems.